Search for b -hadron decays to long-lived particles in the CMS endcap muon detectors - Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Dragicevic,M; Giordano,C; Hussain,PS; Jeitler,M; Krammer,N; et al. (Physical Review D, 2026)
A search for long-lived particles originating from the decay of <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mi>b</a:mi> </a:math> hadrons produced in proton-proton collisions with a center-of-mass energy of 13 TeV at the LHC is presented. The analysis is performed on a dataset recorded in 2018, corresponding to an integrated luminosity of <c:math xmlns:c="http://www.w3.org/1998/Math/MathML" display="inline"> <c:mn>41.6</c:mn> <c:mtext> </c:mtext> <c:mtext> </c:mtext> <c:msup> <c:mi>fb</c:mi> <c:mrow> <c:mo>−</c:mo> <c:mn>1</c:mn> </c:mrow> </c:msup> </c:math> . Interactions of the long-lived particles in the CMS endcap muon system would create hadronic or electromagnetic showers, producing clusters of detector hits. Selected events contain at least one such high-multiplicity cluster in the muon endcaps and require the presence of a displaced muon. The most stringent upper limits to date on the branching fraction <e:math xmlns:e="http://www.w3.org/1998/Math/MathML" display="inline"> <e:mi mathvariant="script">B</e:mi> <e:mo stretchy="false">(</e:mo> <e:mi>B</e:mi> <e:mo stretchy="false">→</e:mo> <e:mi>K</e:mi>